"The Only Thing You've Managed to Break So Far Is My Heart": An Analysis of Portal's Monstrous Mother GLaDOS. Issue 5 (July 2020) - Harkin, Stephanie
This article interrogates Portal 's monstrous antagonist GLaDOS through a psychoanalytical lens, granting specific attention to her maternal coding. The process of presenting maternal authority as monstrous and in need of containment is a patriarchal practice that reinforces the mother gamer's unwelcome presence within video game culture, outlined through a brief examination of various representational trends regarding the maternal figure in games. These patriarchal signifying practices also operate to preserve broader domestic and societal gendered ideologies. Portal 's projections of maternal monstrousness are located within its villain's taunting dialogue and her all-pervasive presence within the unsettling game space, representative of the reabsorbing maternal body. The application of Julia Kristeva's abjection theory and Barbara Creed's faces of the "monstrous-feminine" inform these observations and the construction of GLaDOS as an abject, abusive, and archaic mother.